Penentuan Kelayakan Lokasi Usaha Franchise Menggunakan Metode AHP dan VIKOR - Vienticentia Imanuwelita; Rekyan Regasari Mardi Putri; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Franchise is a type of businesses that offers various benefits such as the good reputation and the stability of operating procedures. Nevertheless, the franchise business could be closed to bankruptcy, one aspect which influences that fact is the location factor. Site selection that does not meet certain criteria has a direct impact on the failure of the franchise business. The determination of the business location feasibility for the object under study has a computational pattern that is not clear, not directional and not concrete. Therefore, it is important to establish the appropriate business location feasibility supported by proper calculation patterns. This research proposes AHP and VIKOR methods to build system that can answer Multi Criteria Decision Making (MCDM) problem for feasibility of franchise business location. The AHP method is used to derive the weighting value of all criterias, while VIKOR focuses on the ranking of alternative business locations and proposes compromise solution. Based on the testing performance, the highest accuracy obtained is 85% with threshold value of 0,56. The sensitivity of VIKOR value while value is changed derived four alternatives that are sensitive to that change. The final result obtained is the eligibility status of each proposed business location.